Belastungssteuerung im Muskelaufbautraining: Belastungsnormativ Intensität versus Wiederholungszahl - Fröhlich, M.; Schmidtbleicher, D.; Emrich, E. (Deutsche Zeitschrift für Sportmedizin, 2002)
The purpose of this empirical study was: 1st: To evaluate a given relationship between intensity and the number of repetitions over six series in a hypertrophy training. 2nd: To evaluate two different training settings for hypertrohy training (constant load vs. constant repetition). Ten male subjects volunteered for the test. Treatment constant load was characterized by a constant intensity (85 % 1-RM). Treatment constant repetition was controlled by an almost constant number of repetition. Totally, all the subjects had to carry out six series with a 3- minute rest interval between the sets in each of the two settings. The workload was calculated for comparison of these two different training settings. The results are: There exist no fixed relationships between intensity and number of repetitions over six series (1. serie 6.3 ± 1.7 rep., 2. serie 5.0 ± 1.4 rep., 3 serie 3.9 ± 1.5 rep., 4. serie 3.3 ± 1.3 rep., 5. serie 2.9 ± 1.5 rep., 6 Serie 2.1 ± 1.2 rep.; F = 10.86; p < .001). By a constant number of repetitions the load decreased over the six series (1. serie 60.0 ± 7.3 kg, 2. serie 56.5 ± 7.7 kg, 3 serie 54.2 ± 7.3 kg, 4. serie 52.3 ± 7.1 kg, 5. serie 50.5 ± 7.4 kg, 6 serie 49.3 ± 7.5 kg). The workload was significant higher in the treatment constant repetitions than in the treatment consant load (F = 19.76; p < .001).